Affiliate Marketing For Dummies - Sudol, Ted; Mladjenovic, Paul; Mladjenovic, Paul J. (For Dummies, 2019)
Get Your Piece of the Hottest Business Online Today! Affiliate marketing is your route to earning some serious bucks. Thousands of companies both large and small like Amazon, Sears, Best Buy, Overstock, Lowe's, Priceline and others have programs so you can profit from the thousands of products they offer. Affiliate marketing is ideal for bloggers looking to monetize their work. This is a multibillion-dollar market, and there are 10+ million people involved in the biz worldwide. There's always room for more because the opportunity keeps growing as more and more companies offer affiliate programs. Affiliate Marketing For Dummies shows you how to get a slice of the pie! Choose the right affiliate product or service for you Find the best affiliate programs for you Find the best affiliate marketing strategies Affiliate Marketing for Dummies is your friendly step-by-step guide to getting in on this moneymaker-big time.
Online resource; Title from title page (viewed December 12, 2019)
Keywords: Affiliate programs (World Wide Web); Internet marketing; Programmes d'affiliation (Web); Marketing sur Internet